The innovator's guide to growth : putting disruptive innovation to work - Anthony, Scott D. (Harvard Business Press, 2008)
More than a decade ago 'The Innovator's Dilemma' illustrated how disruptive innovations drive industry transformation and market creation. This volume extends Christensen's research, demonstrating further how growth-seeking incumbents must develop the capability to deflect disruptive attacks and seize disruptive opportunities.